Analisis Pola Perilaku Peternak Domba Rakyat di Desa Sukawening, Dramaga, Bogor - Zarifa Olivia; Yannefri Bakhtiar; Amiruddin Saleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Sukawening Village is a village with excellent natural potential. The number of sheep farmers in Sukawening Village was originally 15 breeders, but currently there are only 4 breeders left, namely Mr. Ujang, Mr. Haerudin, Mr. Ranta, and Mr. Manim. Analysis of the behavior patterns of the peoples sheep Sukawening Village was carried out to observe the behavior patterns of the peoples farmers in implementing sheep maintenance management, such as the application of good farming practice (GFP) properly. The analysis of peoples sheep behavior patterns in Sukawening Village was carried out through direct interviews by interviewers and interviewees by asking questions related to sheep rearing management. Good sheep raising by following the standards in the GFP, such as pens and equipment, breeds and reproduction, feed and drinking water, management, and animal health. Pak Haerudin is a sheep breeder of Sukawening Village who has implemented several GFPs properly, such as applications in cages and equipment, feed and drinking water, and their management. Peoples sheep breeders in Sukawening Village carry out traditional maintenance management and have not been touched by knowledge either in terms of maintenance or marketing. Keywords: Good Farming practice (GFP), smallholder sheep breeder